Salivary immunoglobulin A response to a match in top-level Brazilian soccer players - Moreira, A.; Arsati, F.; Ramos Cury, P.; Franciscon, C.; Roberto de Oliveira, P.; Cavalcanti de Araujo, V. (The Journal of Strength and Conditioning Research, 2009)
It has been suggested that several parameters of mucosal immunity, including salivary immunoglobulin A (s-IgA), are affected by heavy exercise either in field sports or in the laboratory environment. Few observations have been made during a true sporting environment, particularly in professional soccer. We tested the hypothesis that salivary IgA levels will be decreased after a 70-minute regulation in a top-level professional soccer friendly match. Saliva samples from 24 male professional soccer players collected before and after the match were analyzed. Salivary immunoglobulin A concentration was measured by enzyme-linked immunosorbent assay and expressed as the absolute concentration (s-IgAabs), s-IgA relative to total protein concentration (IgA-Pro), and the secretion rate of IgA (s-IgArate). Rate of perceived exertion (RPE) was used to monitor the exercise intensity. The paired t-test showed no significant changes in s-IgAabs and s-IgArate (p > 0.05) from PRE to POST match. However, a significant (p < 0.05) increase in total protein concentration (1.46 ± 0.4 to 2.00 ± 07) and a decrease in IgA-Pro were observed. The best and most significant correlation was obtained with the RPE and changes in IgA-Pro (rs = -0.43) and could indicate that this expression may be an interesting marker of intensity in a soccer match. However, further investigation regarding exercise intensity, protein concentration, and immune suppression, particularly in team sports, is warranted. From a practical application, the variability of the responses among the players leads us to suggest that there is a need to individually analyze the results with team sports. Some athletes showed a decrease in s-IgA expressions, suggesting the need for taking protective actions to minimize contact with cold viruses or even reducing the training load.